Peran Mathematical Resilience terhadap Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Dasar pada Materi Pecahan - Leni Maulani (Idarotuna : Journal of Administrative Science, 2025)
This study aims to examine the effect of mathematical resilience on students' mathematical problem-solving abilities in the topic of fractions at the Madrasah Ibtidaiyah (MI) level. The research employed a quantitative non-experimental approach with a simple linear regression design. The sample consisted of 32 fourth-grade MI students in Garut Regency, West Java. The instruments used were a 20-item Likert-scale mathematical resilience questionnaire and a set of five open-ended mathematical problem-solving questions based on Polya’s problem-solving steps. The residual normality test using the Shapiro-Wilk method showed a normal distribution with a significance value of 0.137. The regression analysis revealed that mathematical resilience had a significant effect on mathematical problem-solving ability, with a significance value of 0.002 < 0.05. The coefficient of determination (R²) was 0.275, indicating that mathematical resilience contributed 27.5% to the students’ mathematical problem-solving ability. Thus, the higher the students' mathematical resilience, the better their ability to solve mathematical problems.